Nanoencapsulation of betamethasone valerate using high pressure homogenization–solvent evaporation technique: optimization of formulation and process parameters for efficient dermal targeting. (1st February 2019) - Md, Shadab; Kuldeep Singh, Jasvinder Kaur A/P; Waqas, Muhammad; Pandey, Manisha; Choudhury, Hira; Habib, Haroon; Hussain, Fahad; Hussain, Zahid
Abstract: Betamethsone valerate (BMV), a medium potency topical corticosteroid, is one of the most commonly employed pharmacological agents for the management of atopic dermatitis in both adults and children. Despite having remarkable pharmacological efficacy, these agents have limited clinical implication due to poor penetration across the startum cornum (SC). To mitigate issues related to targeted delivery, stability, and solubility as well as to potentiate therapeutic and clinical implication, the nanodelivery systems have gained remarkable recognition. Therefore, this study was aimed to encapsulate BMV into the chitosan nanoparticles (CS-NPs) for optimum dermal targeting and improved penetration across the SC. The prepared NPs were characterized for particle size, zeta potential, polydispersity index, entrapment efficiency, loading capacity, crystallinity, thermal behavior, morphology, in vitro release kinetics, drug permeation across the SC, and percentage of drug retained into various skin layers. Results showed that optimized BMV-CS-NPs exhibited optimum physicochemical characteristics including small particle size (< 250 ± 28 nm), higher zeta potential (+58 ± 8 mV), and high entrapment efficiency (86 ± 5.6%) and loading capacity (34 ± 7.2%). The in vitro release study revealed that BMV-CS-NPs displayed Fickian-diffusion type mechanism of release in simulated skin surface (pH 5.5). Drug permeation efficiency and the amount of BMV retained into the epidermis and the dermis were comparatively higher in case of BMV-CS-NPs compared to BMV solution. Conclusively, we anticipated that BMV-CS-NPs could be a promising nanodelivery system for efficient dermal targeting of BMV and improved anti-AD efficacy.